Women's Leadership in Education: thematic analysis of the Qur'an and Hadith - Vina Maula Rohmatika; Abdul Syukkur (STAI Syaichona Moh. Cholil Bangkalan, 2024)
The main objective of this article is to explain women’s leadership in the study of Qur’anic and hadith interpretation. This study is a library research using the method of collecting bibliographic data, Reading and taking notes according to the research title, and processing research materials. Primary data sources include books on interpretations of the Qur’an and the Sunnah, as well as contemporary fatwas on women. Data analysis includes data reduction, data presentation, and conclusion drawing. The research concludes that the Qur’an does not explicitly prohibit female leadership, even showing examples such as Queen Balqis (An-Naml 29-35) who led wisely. Leadership is based more on a person’s qualities and abilities (capabilities) than on gender. Although there are verses interpreting the role of men as family leaders (An-Nisa 34), which have become the basis of debate, many modern scholars interpret it in the context of responsibility, not absolute superiority.